2003
DOI: 10.3136/fstr.9.350
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Japanese Green Tea Extract Using GC/O with Original Aroma Simultaneously Input to the Sniffing Port Method (OASIS)

Abstract: Recent studies of natural aromas have focused on only the lowest odor threshold compounds. In this study, we evaluated the volatile compounds of Japanese green tea, comparing the original aroma simultaneously input to the sniffing port method (OASIS) with the aroma extract dilution analysis method (AEDA). Geraniol, indole and linalool were classified in the low odor threshold by AEDA. Using OASIS, geraniol showed enhancement of the green character and indole showed strengthening the overall green tea odor, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 14 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…Potent odorants of green tea made in China and Japan were meaty, metallic, fatty, honey-like, floral, and animal-like (Guth et al, 1993;Kumazawa et al 1999, Hattori et al 2003, 2005. In this study, we confirmed the potent characters of Sencha were green and fresh green.…”
Section: Comparison Of the Volatile Compounds In Each Tea Samplesupporting
confidence: 70%
See 2 more Smart Citations
“…Potent odorants of green tea made in China and Japan were meaty, metallic, fatty, honey-like, floral, and animal-like (Guth et al, 1993;Kumazawa et al 1999, Hattori et al 2003, 2005. In this study, we confirmed the potent characters of Sencha were green and fresh green.…”
Section: Comparison Of the Volatile Compounds In Each Tea Samplesupporting
confidence: 70%
“…Indole (peak 21) highly contributed (FD f =4 5 ) to the floral aroma and strengthened the overall green tea odour (Hattori et al 2003(Hattori et al , 2005. Moreover, there was a large difference in the amount of indole between LTPGT and NTPGT.…”
Section: Comparison Of the Volatile Compounds In Each Tea Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have studied the aroma characteristics of teas, and to date more than 600 volatile compounds have been identified [1]. Recently, it was reported that the green note, but not the floral note, of tea is emphasized by the addition of a specific concentration (from 1 ppb to 10 ppb) of geraniol (floral odor) to green tea infusion [2]. The intricate mechanism of odorant reception [3,4] suggests that complex odors such as tea odor are created by the interaction of individual compounds.…”
mentioning
confidence: 99%
“…In this study, we compared SWE to conventional heated water extraction and pressurized extraction. In addition, we simultaneously evaluated differences in the taste and flavor of green tea extracts from each extraction method (Hattori et al, 2003). Sensory evaluation results suggested that the strong unpleasant taste peculiar to catechins was decreased by SWE.…”
Section: Introductionmentioning
confidence: 99%